2016
DOI: 10.3389/fgene.2015.00351
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Cellular Dynamics in Epidermal Growth Factor Signaling Using a New Pathway-Based Integration Approach for Proteomics and Transcriptomics Data

Abstract: Identification of dynamic signaling mechanisms on different cellular layers is now facilitated as the increased usage of various high-throughput techniques goes along with decreasing costs for individual experiments. A lot of these signaling mechanisms are known to be coordinated by their dynamics, turning time-course data sets into valuable information sources for inference of regulatory mechanisms. However, the combined analysis of parallel time-course measurements from different high-throughput platforms st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Also in relation to PRKAR2B , we found that CsA reduced the level of its expression, which is consistent with the observations of Zgheib et al [ 81 ]. This gene encodes regulatory subunit of the cAMP-dependent protein kinases [ 82 ]; the increased expression of which is associated with the tumor cells obtaining a higher metastatic potential by induction of EMT [ 83 , 84 ]. Therefore, the silencing of SKP2 and PRKR2B after the addition of cyclosporin A may confirm its anti-inflammatory properties and efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Also in relation to PRKAR2B , we found that CsA reduced the level of its expression, which is consistent with the observations of Zgheib et al [ 81 ]. This gene encodes regulatory subunit of the cAMP-dependent protein kinases [ 82 ]; the increased expression of which is associated with the tumor cells obtaining a higher metastatic potential by induction of EMT [ 83 , 84 ]. Therefore, the silencing of SKP2 and PRKR2B after the addition of cyclosporin A may confirm its anti-inflammatory properties and efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…To address this challenge, methods to integrate heterogeneous data sources such as transcriptomic and proteomic data sets have been proposed (Haider and Pal, 2013 ). These integration methods range from naive weighted means of transcript and protein abundances (Balbin et al, 2013 ) to consensus pathways and molecules (Wachter and Beißbarth, 2016 ). Other approaches take advantage of the relationships between gene products to produce a network of associated genes, known as an interactome (Gibbs et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…A time-resolved study demonstrating different temporal modes of RNA-and protein-layer regulations in response to misfolding stress in mammalian cells was published recently by Cheng et al (2016). Following time-series data on different molecular layers thus clearly adds information with the potential to decipher molecular mechanisms in more detail (Wachter and Beißbarth, 2016).…”
Section: Introductionmentioning
confidence: 99%